Amaurosis and contralateral cranial nerve pairs III and VI paralysis after peribulbar block - Case report - Leme,Fábio Caetano Oliveira (2018)
Abstract Background and objectives: Peribulbar anesthesia has emerged as a safer option compared with intraconal retrobulbar block. Still, peribulbar anesthesia may not be considered without risk. Numerous complications have been described when performing this technique. This report aims to describe a rare case of amaurosis and contralateral paralysis while attempting to perform a peribulbar anesthesia. Case report: Male patient, 75-year old, physical status ASA II, undergoing cataract surgery by phacoemulsification with intraocular lens implantation. Sedated with fentanyl and midazolam and subjected to peribulbar anesthesia. There were no complications during surgery. After finishing the procedure, the patient reported lack of vision in the contralateral eye. Akinesia of the muscles innervated by the cranial nerve pairs III and VI, ptosis, and medium-sized pupils unresponsive to light stimulus were observed. Four hours after anesthesia, complete recovery of vision and eyelid and eyeball movements was seen in the non-operated eye. Conclusions: During peribulbar anesthesia, structures located in the intraconal space can be accidentally hit leading to complications such as described in the above report. Following the technical guidelines and using appropriate size needles may reduce the risk of such complication, but not completely.